(3CfhGQ GdJfRjd hCSQGQ GdJChjds - (3GdHjVGhj, CHh SYjO, CHh GdNjQ, fGUQ GdOjf, YHO Gddg Hf YeQ Hf eMeO Hf Ydj(B685(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj fRd GdaQbGf Ydi YHOg djchf ddYGdejf fPjQG hHYO aEf CYXe GdYdhe ebOGQG hCQaYgG TQaG hefGQG ShQI aGJMI GdcJGH hJSei Ce GdbQBfs
(3BNQgG (B:s
(3ef bQC ShQI Gdcga ef BNQgG cGfJ dg fhQG ef bQfg Edi bOeg hef bQCgG cdgG cGfJ dg fhQG ef GdCQV Edi GdSeGA JeJ GdfUa GdChds
(3HChdgG agQSs
(3JHUQI GdYfhGf (B:s
(3JaSjQ GdHjVGhjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4/109s
(3cTa GdXfhf (B1/186s
Keywords: (3GdJaSjQ hYdhe GdbQBfs